Islamic paradigms for women’s education and their roles to bring up Tawhidic Ummah - Abd Rashid, Adnan (2010)
From the Islamic perspective, man and woman are not come to this world accidentally without any mission and purpose in his life. This principle is clearly laid down in the Qur’an: “Did you think that We had created you in play (without any purpose), and that you would not be brought back to Us?” This verse makes the point that man and woman have to realise that their existence in this worldly life is very precious. In addition, he or she has a particular mission and vision, duties and messages, which need to be performed in both his life in this world and the life to come in the Hereafter because he or she will be returned to his/her Lord to face the consequences of his actions. Hence, education is crucial for every individual Muslim whether man and woman concerned with a comprehensive development in order to achieve a successful life in this world and salvation in the Hereafter. Education are crucial ways in which to know and believe in Allah, the effective means to develop good character and the right way to cope with worldly life. This evidence shows that from the very beginning of the revelation, Islam has been very concerned about knowledge and education rather than any other aspects; “Iqra’” It means that from the Islamic point of view, the development of intellectual and good moral qualities through divine guidance constituted the foremost programme existing in human. This means that education is mainly to develop man and woman to seek virtue in accordance with the Din al-Islam which has no conflict with human’s worldly life. Education system may lead an individual toward the full extent of his potentialities and abilities in gaining knowledge by conforming to good moral values as well as legal precepts. If we refer to the Hadith, “Every new-born child is born in a state of fitrah. Then his parents make him a Jew, a Christian or a Magian, just as an animal born intact. Do you observe any among them that are maimed (at birth)?,” which signifies that the parent’s role and their responsibility for transmitting the knowledge of tawhid is crucial, as well as for feeding, clothing etc. This means that Muslim parents particularly woman may inculcate the way of the Sunnah, such as the recitation of supplications (duca’), during the activities of feeding, clothing and so on, the recognition of halal and haram in these activities and the cultivation of other aspects of education. These are the roles and ways of woman bringing up her children. This deliberation may give a picture of the nature of education, which takes its aim from beyond the excellence of the intellect. The effects of this education may lead Muslims to deal with their knowledge for the benefit of themselves and for others in accordance with the teaching of Islam which is concerned with the development of the whole range of human faculties, both physical and spiritual, and the development of society of balanced growth. Indeed, this atmosphere may enable every individual Muslim voluntarily to surrender himself to Allah whole-heartedly and maintain his dignity and superiority as a servant and vicegerent of Allah in this world and further, to attain felicity and prosperity in the Hereafter. This concept paper attempts to examine and discuss the efforts how woman’s education is important and how she able to play her roles to facilitate this type of education to bring up Tawhidic Ummah.